ANALISIS FAKTOR YANG MEMPENGARUHI JAMAAH UMRAH DALAM MENGAMBIL KEPUTUSAN PENGGUNAAN TRAVEL UMRAH FAIRUZ TOUR PALEMBANG - Wulan Purnama Sari; Nuraida Nuraida; Candra Darmawan; Nurseri Hasnah Nasution (Program Studi Manajemen Dakwah, Fakultas Dakwah dan Komunikasi, UIN Raden Fatah Palembang, 2022)
The problem taken from this research is that the high number of Umrah pilgrims each year causes the number of pilgrims on the Fairuz Tour Palembang Umrah travel to fluctuate. This is because when making decisions on the use of Umrah travel, many Umrah travel services do not meet regulations, so many factors are taken into consideration by pilgrims. This study aims to determine whether there are individual factors, environmental factors, and marketing stimulus factors that influence Umrah pilgrims in making decisions about using Fairuz Tour Palembang Umrah travel. In this study, researchers analyzed the factors that influence Umrah pilgrims in making decisions about the use of Fairuz Tour Palembang Umrah travel. Respondents in this study were pilgrims who had performed Umrah using Fairuz Tour Palembang Umrah travel with the use of the data used in this study, namely primary data obtained directly from respondents by filling out questionnaires. Then analyze the data obtained in the form of quantitative analysis. Quantitative analysis includes validity test, reliability test, classical assumption test, multiple linear regression analysis, with partial test (T test), simultaneous test (F test), and determinant test (R2). with a significance level of 0.1. From the results of this study indicate that all the independent variables tested have a positive and significant effect on consumer decisions with the F test and t test while the Adjusted R Square number of 0.414 indicates 41.4% variation in consumer decisions obtained from the three independent variables where the remaining 68, 6% is explained by other factors outside this study. Keywords: Individual Factors, Environmental Factors, Marketing Stimulus Factors, Consumer Decision